ENGLISH VOWELS AND CONSONANTS MISPRONUNCIATION OF THE SEVENTH PRESIDENT OF REPUBLIC OF INDONESIA IN HIS OFFICIAL ENGLISH SPEECHES AND ITS INFLUENCING FACTORS - Ambalegin Ambalegin; Tomi Arianto (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
This research aimed to find out the mispronunciation of English vowels and consonants of the seventh president of Republic of Indonesia, Mr. Joko Widodo in his official English speeches based on the standard of British English Received Pronunciation (RP) and the factors influencing his English vowels and consonants mispronunciation. This research is a descriptive qualitative research. In collecting data, the researchers used observation method with non-participatory technique (Sudaryanto, 2015). In analyzing the data, the researchers used articulatory identity method (Sudaryanto, 2015). It was found that the consonant sounds /θ/, /ð/, /v/, /z/, /ʃ/ were pronounced incorrectly, the vowel sounds/ə/, /ɒ/, /ɛ/, /i/, /e/, /ɪ/ were pronounced inconsistently, and the diphthong sounds /ɪə/, /eɪ/, /əʊ/ and /aʊ/ were pronounced incorrectly. The consonant sound /l/ in the middle of the word was not pronounced. The consonant sound /j/ in the middle of the word is omitted. The consonant sounds /g/, /tʃ/, and /r/ were pronounced the same as the spelling. The consonant sounds /t/, /s/, /k/ at the end of the words were omitted. The letter y sounded /ɪ/ at the end of the word was pronounced as /e/. The diphthong sounds /ɪə/, /eɪ/, /əʊ/ and /aʊ/ were pronounced as /ɪ/, /ʌ/, /ɛ/, /ə/, /e/, and /ͻ/. The factors influencing the mispronunciation of English vowel and consonant sounds were mother tongue interference, sound system differences between Indonesian and English, the influence of spelling on pronunciation, educational background, and environmental background.